Desain Pembangkit Listrik Tenaga Air Kapasitas 5 kW Di Desa Siabu Kabupaten Kampar Riau - Sintong, Sintong; Hamzah, Amir (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Power Plant Design Village Siabu water in Kampar, Riau based on the electrical energy needs of the villagers Siabu that there are not fulfilled. Design and Construction of Hydroelectric Power 5 kW capacity is located in the village of Siabu Regency, Riau Kampar by utilizing the flow of the river from the springs Siabu Bukit Barisan area. In this study, water discharge measurements using floating and height measurements falling water using water fitting. From measurements of water discharge and high falling water, is used to determine the design of hydroelectric plants that include pipe dimensions rapidly, kind of water turbines dimensional water turbine, and to determine the capacity of a synchronous generator 3 phase that corresponds to the design of hydropower generation capacity of 5 kW. The calculations show that the potential power that can be generated in Hydroelectric Power Plant in the Village this Siabu theoretically amounted to 5.432 kW to discharge water used by 0.4196 m3 / s and a height of fall of water (head nett) 3 meters. Of discharge water and high water fall is obtained rapidly design pipe with a length of 5 meters and a diameter of 0.3651 meters and turbine diameter dimensions of 30 cm by 163 cm width. From the calculation power of 5.432 kW aroused the 3 phase synchronous generator capacity that is used by 7 kVA.Keywords: Water Discharge, The Height of The Water Fall (Head), Hydropower Capacity of 5 kW, Power Potential, Water Turbine, Generator